Effects of Actinomycete Secondary Metabolites on Sediment Microbial Communities - Patin, Nastassia V. (Appl Environ Microbiol, 2017)
Marine sediments harbor complex microbial communities that remain poorly studied relative to other biomes such as seawater. Moreover, bacteria in these communities produce antibiotics and other bioactive secondary metabolites, yet little is known about how these compounds affect microbial community structure. In this study, we used next-generation amplicon sequencing to assess native microbial community composition in shallow tropical marine sediments. The results revealed complex communities comprised of largely uncultured taxa, with considerable spatial heterogeneity and known antibiotic producers comprising only a small fraction of the total diversity. Organic extracts from cultured strains of the sediment-dwelling actinomycete genus Salinispora were then used in mesocosm studies to address how secondary metabolites shape sediment community composition. We identified predatory bacteria and other taxa that were consistently reduced in the extract-treated mesocosms, suggesting that they may be the targets of allelopathic interactions. We tested related taxa for extract sensitivity and found general agreement with the culture-independent results. Conversely, several taxa were enriched in the extract-treated mesocosms, suggesting that some bacteria benefited from the interactions. The results provide evidence that bacterial secondary metabolites can have complex and significant effects on sediment microbial communities. IMPORTANCE Ocean sediments represent one of Earth's largest and most poorly studied biomes. These habitats are characterized by complex microbial communities where competition for space and nutrients can be intense. This study addressed the hypothesis that secondary metabolites produced by the sediment-inhabiting actinomycete Salinispora arenicola affect community composition and thus mediate interactions among competing microbes. Next-generation amplicon sequencing of mesocosm experiments revealed complex communities that shifted following exposure to S. arenicola extracts. The results reveal that certain predatory bacteria were consistently less abundant following exposure to extracts, suggesting that microbial metabolites mediate competitive interactions. Other taxa increased in relative abundance, suggesting a benefit from the extracts themselves or the resulting changes in the community. This study takes a first step toward assessing the impacts of bacterial metabolites on sediment microbial communities. The results provide insight into how low-abundance organisms may help structure microbial communities in ocean sediments.